Assessing the Factors Influencing the Food Grain Production in Andhra Pradesh: District Wise Analysis - I. V. Y.Rama Rao,; V. T.Raju, (Journal of Agricultural Extension Management, 2025)
India is one of the leading Food grains producing countries of the world with cultivated area of 121.91 Million hectares and production of 212.03 Million tonnes during 2001-02. India exports and imports Food grains and their products to and from many countries. In India, leading states in Food grains production are Utter Pradesh, Punjab, and West Bengal. Andhra Pradesh is ranked fifth, with cultivated area of 7 .04 Million hectares and production of 14.84 Million tonnes during 2001-02#. Further, in Andhra Pradesh region wise descending order of Food grain production was Coastal Andhra, Telangana and Rayalaseema with respective production of 8.24, 6.46 and 1.33 Million Tonnes. The findings of the studies by Hazell (1984) Jayadevan (1991) revealed that the growth in crop production during the post-green revolution period has been accompanied with increased instability and yield fluctuation turned out to be the major source of production instability